Paleoindian Occupation in the Central Mountains of Argentina: Was It a Failed Colonization? - Rivero, Diego Eduardo (2011)
The aim of this report is to present information about human presence during the Pleistocene/Holocene transition in the Central Mountains of Argentina and to discuss its implications for the peopling of the Southern Cone of South America. The Central Mountains are located in Córdoba and San Luis provinces, in central Argentina.